Late-onset phenotype associated with a homozygous GJC2 missense mutation in a Turkish family. (September 2019) - Kuipers, Demy J.S.; Tufekcioglu, Zeynep; Bilgiç, Başar; Olgiati, Simone; Dremmen, Marjolein H.G.; van IJcken, Wilfred F.J.; Breedveld, Guido J.; Mancini, Grazia M.S.; Hanagasi, Haşmet A.; Emre, Murat; Bonifati, Vincenzo
Abstract: Objective: Recessive mutations in the Gap Junction Protein Gamma 2 ( GJC2 ) gene cause Pelizaeus-Merzbacher-like disease type 1, a severe infantile-onset hypomyelinating leukodystrophy. Milder, late-onset phenotypes including complicated spastic paraplegia in one family (SPG44), and mild tremor in one case, were reported associated to GJC2 homozygous missense mutations. Here, we report a new family with two siblings carrying a different homozygous GJC2 mutation, presenting with late-onset ataxic and pyramidal disturbances, and parkinsonism in one of them. Methods: Two affected siblings were studied by neurological examination and brain MRI. Genetic analyses included genome-wide homozygosity mapping in both siblings, and whole exome sequencing in one sib. The resulting candidate gene variant was validated by Sanger sequencing. Results: The affected siblings share a novel homozygous GJC2 missense mutation (c.820G>C, p.Val274Leu), predicted as pathogenic by all used in-silico tools. Brain MRI showed hyperintense signal in T2-weighted images in the internal capsule and subcortical and periventricular white matter, consistent with hypomyelination. Conclusions: Our findings confirm and further expand the late-onset phenotypes of GJC2 mutations, to include prominent ataxia, pyramidal disturbances and mild parkinsonism, and confirm the distinctive associated MRI pattern. Highlights: We report a new missense Gap Junction Protein Gamma 2 ( GJC2 ) mutation associated with an unusual, late-onset phenotype. This phenotype includes ataxia, pyramidal disturbances and parkinsonism. GJC2 should be considered in patients with similar, late-onset, unexplained phenotypes.